Antitumoral Properties of a Pincer-Type Isonicotinohydrazone-Hg(II) Complex - Burcu Saygıdeğer Demir; Aycan Sezan; Ezgi Derinöz; Eylem Nas; Mehmet Özerten; Ghodrat Mahmoudi; Yasemin Saygıdeğer (European Journal of Biology)
Objective: The aim of this study was to evaluate the antitumoral properties of the novel Hg(SCN)2 complex of a pincer-type isonicotinohyrazone ligand (PTIH). Materials and Methods: Hydrazine ligands were prepared through a Schiff base condensation between the 2-Acetylpyridine and isonicotinoyl acid hydrazide. PTIH was synthetized by a branch tube method using Hg(SCN)2. In vitro cell killing activity, the induction of apoptosis, the influence on motility, and the effects on mRNA expression to a motility-related gene (E-cadherin) of PTIH were evaluated in A549, HepG2, HUH7 cancer cell lines, and BEAS2B non-cancer cell line. Results: PTIH was found to be cytotoxic to cancer cells, compared to non-cancers, and induced apoptosis. Additionally, it suppressed cell migration in A549 cells, leading to an increase in the levels of E-cadherin mRNA expression, and decreased colony formation in HepG2 and HUH7 cells. Through UV titration studies, it was determined that PTIH showed albumin binding and interacted with DNA by electrostatically and/or groove binding. Conclusion: PTIH exerted more cytotoxic effects in some cancer cells than in normal cells. This feature and other anticancer properties make it a promising agent.